(untitled) (قضايا سياسية, 2023)
The impact of the technological revolution’s penetration into the various spheres of life was not limited to the political, economic and societal interactions of states and individuals. Rather, it extended to the creation of a new arena of unconventional wars, far from the arenas of land, sea and air. The new arena of conflict is the cyber domain. The latter presented a new set of elements that incentivised state and non-state actors to use them as a tool of competition, domination, conflict, and unconventional terrorism, to the extent that it may move the world from various electronic attacks to a “cyber war.” Russia is among the first countries to use cyber capabilities in the military field, as it has been interested in developing and increasing its offensive capabilities in this field since 1998. The Russian strategy in its conflict with Ukraine relies on offensive electronic weapons as a power multiplier in wars, meaning that it increases the combat capabilities of the state if it is used alongside other military capabilities. This strategy also relies on hindering the opponent's information infrastructure and its military and civil communications before embarking on military operations.